New Late Cretaceous fruit and its seeds from the Ingersoll Shale (eastern Alabama, U.S.A.) indicate affinity with Ranunculaceae (Ranunculales) - Brian J. Axsmith; Debra Z. Stults; Wei Wang; Lisa D. Boucher (Acta Palaeobotanica)
We describe a new ranunculacean fruit from Ingersoll Shale sediments (Santonian, 85.5 to 83.5 Ma), a part of the Eutaw Formation as it occurs in eastern Alabama. The Ranunculales/Ranunculaceae are basal eudicots but their fossil record is not well documented which is most likely due to their taxa being predominantly herbaceous and therefore lacking a propensity for fossilization. Two fruits are in evidence, one is a mature fruit in the process of dehiscence and in which several seeds are describable, and the other is interpreted as a less mature fruit. From these fruits, we describe a new genus, Costellifructus Axsmith, Stults, Wang, et Boucher gen. nov., and species, Costellifructus alabamensis Axsmith, Stults, Wang et Boucher sp. nov. Both fruits are urceolate and display follicles that are fused at the base and maintain this fusion through the length of the main body of the fruit thus forming a capsule. The fusion of follicles is denoted by areas of depression on the fruit. Especially observable in the large fruit are follicular ridges which continue into long stylar extensions. Interestingly, this is a character which is also very recognizable on extant ranunculacean genera such as Aquilegia L. and Delphinium Tourn. ex L. Seeds are characterized as small (2.5 × 2 mm), rugose, ridged, obovate longitudinally, and trigonal in cross-section profile, properties fitting within some ranunculacean taxa.